Type Synthesis of 2T2R Parallel Mechanisms Based on Optimal Transmission - Mao Jiang; Zhu Xiaofei; Chen Jin; Cai Wenlai (Jixie chuandong)
To synthesize a class of 2T2R parallel mechanisms with optimal transmission and large tilting ability, a type synthesis method for parallel mechanisms is proposed by combining the screw theory and the limb construction method. Taking the 2-RPS mechanism as the basic limb, the screw theory is used to classify the constraint types of the new limb, and the limb construction criterion is given to ensure that the degrees of freedom of the parallel mechanism remain unchanged. Combined with the characteristics of motion/force transmission of the mechanism, the limb with the maximum transmission index is selected by using the screw theory, and the 2T2R parallel mechanism with the optimal transmission is synthesized. Finally, the kinematics analysis of a novel 2-RPS-UPS parallel mechanism is carried out, and the workspace of the mechanism is solved by Matlab. The results show that the synthesized parallel mechanism has optimal transmission and large tilting ability.